Microstrip Antenna with Split Circular Ring Shaped DGS Structure for WLAN Applications (International Journal of Communication Systems and Network Technologies, 2018)
Paper is outcome of DGS inspired antenna which was proposed for the WLAN applications of S band. Proposed antenna is designed at 1.8GHz frequency. DGS of split ring shaped structure was implemented later to modify the antenna characteristics. Modified results increases the return loss up to -37dB from -12dB and increased the bandwidth to 41.4MHz from 38MMHz.
Keywords: Defected Ground Structure (DGS); Microstrip Patch Antenna (MPA); Split Ring Structure (SRS); Computer Simulation Technology (CST)